Sport and technology: An actor-network theory perspective - Kerr, Roslyn (Globalizing Sport Studies, 2016)
How do new technologies come to be used in sport? This book moves beyond the idea of functionality to explore the many other important factors that athletes and sporting bodies consider throughout the process of adoption. Few would question the difficulty of producing an elite athletic performance. The high level of training, combined with intense competition and pressure from media and sponsors, can be challenging for athletes and sporting bodies to negotiate. The book investigates how these factors affect the use of technology in sport, while simultaneously demonstrating the influence of new technologies on sporting practice. Using actor-network theory - an approach common in studies of science and management but seldom applied in this field - it offers readers an inside view into elite sport and the part that technology plays in training, competition and broadcasting.